STRATEGI MANAJEMEN KEUANGAN UNTUK OPTIMALISASI PENGELOLAAN INCOME PADA KARYAWAN MEDIS DAN NON MEDIS RS. MEDIKA BSD DI ERA MILLENIAL - Sri Mardiana; Wawan Supriyatna; Zakaria Zakaria (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Family financial management (financial planning and control) is another shape of financial management application. Knowledge of financial management is not only required for the enterprises, but also important to apply for others forms such as family, household or individual (as employee). Not only companies that absolutely must manage their finances well, each individual must also be adept at managing his finances so that income and expenses can run in a balanced manner. Lack of knowledge about financial planning is a serious problem for Indonesian at this time, even most people do not manage their finance properly. So that why mostly the families do not have an emergency fund for emergency purposes. An established family is the dream of the whole family, but to achieve financial stability is not easy, because not all families have a large income. For this reason, it is necessary to have a strategy to manage finances well by making financial planning so the income can be used optimally.Keywords: Financial management strategies, Optimizing Income Management, Medical and NonMedical Employees at BSD Medika Hospital